Women’s Rights in the People’s Republic of China and the Republic of China in Taiwan in the Early XXI Century. A comparative analysis - Kosmala, Weronika (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
Over the past century, the People's Republic of China and the Republic of China in Taiwan have gone through completely different processes of political, social and economic development. The differences between these entities can be seen not only in the political system, but also in the situation of women. Both the People's Republic of China and the Republic of China in Taiwan are influenced by the ideas of Confucianism and the patriarchal model of family and society, however, the process of the formation of women's rights and the growth of gender equality can be found in their history. The purpose of the paper is to show the extent to which the degree of women's equality in the two areas differs, and to identify the reasons for the existence of these antinomies. The paper uses a comparative method to show the differences between the PRC and the Republic of China in terms of both the system and the degree of gender equality, and a content analysis of sources on the subject and the literature on the subject. Silhouettes of women in the public sphere of China and Taiwan are also presented, using the example of Taiwanese President Tsai Ing-Wen and First Lady of the People's Republic of China Peng Liyuan, who are present in politics. The thesis of the paper is that the degree of equality for women in the People's Republic of China and the Republic of China in Taiwan differs, despite the influence of Confucianism and the patriarchal family model found in both countries. The article aims to answer the research questions: Does the degree of women's equality in the People's Republic of China differ from that of women in the Republic of China in Taiwan? What are the reasons for the differences in the degree of women's equality in these areas? What factors affect the level of gender equality in these countries?